Cognitive inflexibility in Obsessive-Compulsive Disorder. (14th March 2017) - Gruner, Patricia; Pittenger, Christopher
Highlights: Deficits in cognitive flexibility have been described in Obsessive-Compulsive Disorder (OCD). These deficits may contribute to symptomatology. Classical neuropsychological probes test multiple constructs simultaneously. More specific behavioral tests, supplemented by neuroimaging, are needed. Abstract: Obsessive-Compulsive Disorder (OCD) is characterized by maladaptive patterns of repetitive, inflexible cognition and behavior that suggest a lack of cognitive flexibility. Consistent with this clinical observation, many neurocognitive studies suggest behavioral and neurobiological abnormalities in cognitive flexibility in individuals with OCD. Meta-analytic reviews support a pattern of cognitive inflexibility, with effect sizes generally in the medium range. Heterogeneity in assessments and the way underlying constructs have been operationalized point to the need for better standardization across studies, as well as more refined overarching models of cognitive flexibility and executive function (EF). Neuropsychological assessments of cognitive flexibility include measures of attentional set shifting, reversal and alternation, cued task-switching paradigms, cognitive control measures such as the Trail-Making and Stroop tasks, and several measures of motor inhibition. Differences in the cognitive constructs and neural substrates associated with these measures suggest that performance within these different domains should be examined separately. Additional factors, such as the number of consistent trials prior to a shift and whether a shift is explicitly signaled or must be inferred from a change in reward contingencies, may influence performance, and thus mask or accentuate deficits. Several studies have described abnormalities in neural activation in the absence of differences in behavioral performance, suggesting that our behavioral probes may not be adequately sensitive, but also offering important insights into potential compensatory processes. The fact that deficits of moderate effect size are seen across a broad range of classic neuropsychological tests in OCD presents a conceptual challenge, as clinical symptomatology suggests greater specificity. Traditional cognitive probes may not be sufficient to delineate specific domains of deficit in this and other neuropsychiatric disorders; a new generation of behavioral tasks that test more specific underlying constructs, supplemented by neuroimaging to provide insight into the underlying processes, may be needed.